Pollen Viability in Taro (Colocasia esculenta (L.) Schott) in Cuba - Figueroa Aguila, Yadelys; Milián Jiménez, Marilys D.; Rodríguez García, Yuniel (Agrisost ISSN 1025-0247, 2018)
In taro, pollen availability or variability, and the number of clones that produce inflorescences, are not worldwide problems today. However, in Cuba, the appearance of inflorescence is critical, since the high-yielding accessions are not the ones that produce the inflorescences; it rarely or never happens, but when it does, pollen is not viable in most cases. Therefore, the aim of this paper is to evaluate fertility and viability of pollen in taro accessions (Colocasia esculenta). The germplasm accessions of the species, preserved at the Center for Tropical Crops Research (INIVIT) were evaluated during the 2015-2016 period. Staining by aceto-carmine glycerol jelly or pollen viability test was performed to 19 accessions selected for their inflorescences in field conditions. The result was expressed as the percentage with respect to the total number of pollen grains, using a descriptor of variations of pollen viability to determine if the accessions could be used as male parents in crop breeding programs. Five of the nineteen accessions evaluated were observed to produce viable pollen, which may be used as potential male and female progenitors in the genetic breeding program by species hybridation.
Keywords: fertility; pollen; taro; Colocasia esculenta